Cover Picture: Template Design and Economical Strategy for the Synthesis of SSZ‐13 (CHA‐Type) Zeolite as an Excellent Catalyst for the Selective Catalytic Reduction of NOx by Ammonia (ChemCatChem 23/2015). Issue 23 (December 2015) - Xu, Ruinian; Zhang, Runduo; Liu, Ning; Chen, Biaohua; Zhang Qiao, Shi
Abstract : The Front Cover shows a new synthesis and use of the CHA‐type zeolite, SSZ‐13. In their Full Paper, R. Xu et al. demonstrate the outstanding performance of SSZ‐13 for selective catalytic reduction of NO, showing ≈100 % NO conversions across a wide temperature window of 150–450 °C. The CHA‐topology construction was verified by both experimental and computational works: IR spectra, density functional theory (DFT), and potential energy distribution (PED) calculations.